A study on the variability of ionospheric total electron content over the East African low‐latitude region and storm time ionospheric variations. Issue 9 (20th September 2016) - Olwendo, O. J.; Yamazaki, Yosuke; Cilliers, P. J.; Baki, P.; Doherty, P.
Abstract: The variation of total electron content (TEC) derived from the International Global Navigation Satellite Systems Service receiver (formerly IGS) over the East African low‐latitude region from up to 12 observation stations for the period 2012 was analyzed. The diurnal and annual TEC contour plots generated from data over the region show that the equatorial anomaly crests manifest remarkable seasonal variations. The crest of the equatorial ionization anomaly is fully formed and yields the maximum values of TEC during the equinoxes (March/April and September/October) and minimum in the solstice (June/July and November/December). The results of this observation show that the crest develops between 12:00 and 16:00 LT and is greatly dependent on the time when the ionosphere is uplifted at the dip equator via the E × B drift force. The postsunset TEC enhancements at stations away from dip equator depict the ionospheric plasma density diffusion (flow) from the dip equator leading to the formation of ionization anomaly crests that lasts for few hours after the sunset local time. The ionospheric response to the strong geomagnetic storm of the March 2015 has also been examined. The ionospheric response to the geomagnetic storms has shown a strong thermosphere‐ionosphere coupling. The negative storm effect that occurred over the anomaly crest region is more likely due to the composition disturbances associated with high energy deposits. Key Points: The ionospheric dynamics is highly variable at the low latitudes Variations in EEJ control the ionization levels at low latitudes Localized effects contribute to ionospheric dynamics during storms